How we change : (and ten reasons why we don't) - Ellenhorn, Ross D (Harper Wave, an imprint of HarperCollinsPublishers, 2020)
"Many of us are familiar with the tension between wanting to change a behavior pattern and the seeming impossibility of making that change. Whether you're trying to quit smoking, struggling over a diet, or attempting to abstain from another any number of bad habits or negative behavior patterns, we often feel a sense of failure when we don't succeed in making the shift to more positive ones. This often sets off a cascade of bad feelings and discouragement, making it even harder to change. The voice in our head tells us: Why bother? Ross Ellenhorn's approach will forever change our relationship to change. His decades-long career as a pioneer in helping people overcome addiction and psychiatric disorders-especially those for whom the mental healthcare system has failed them-has helped him to develop an effective, long-term method to approach change from the simplest shifts to the most profound. Ellenhorn argues that only by understanding the powerful pull to stay the same, can we begin to make the steps towards change. The problem isn't that we lack the right skills or knowledge to achieve the changes we want to make; instead, successful change depends on our understanding of why we don't change rather than on learning some new strategy to change. The tendency to stay the same is often based on evolutionary coping mechanisms that mess with our greater reasoning about wanting to change. Ellenhorn addresses the 10 Reasons Not to Change and in doing so, he helps us to understand the logic of staying the same, rather than believing our resistance to change is something that is broken inside of us. In HOW WE CHANGE, Dr. Ellenhorn brings his decades of clinical experience and his research on Fear of Hope together to help readers understand the beauty and vunerability inherent both in trying to make a change and staying the same. Ellenhorn speaks to the core of our insecurities and fears about ourselves, both soothing and encouraging the reader. He approaches difficult ideas, like the existential nature of change and fear of failure, with a humor and kindness that will draw readers in and allow them to confront, and ultimately accept, the parts of themselves that keep them from making a change. HOW WE CHANGE is a brilliant and counterintuitive approach that will forever shift our perspective on how to make important and positive changes in our lives by first accepting our resistance to it"--